The practical utility of psychometric scales for the assessment of the impact of posttraumatic scars on mental health - Mekereș, Gabriel Mihai; Buhaș, Camelia Liana; Tudoran, Cristina; Csep, Andrei Nicolae; Tudoran, Mariana; Manole, Felicia; Iova, Claudiu Sorin; Pop, Nicolae Ovidiu; Voiţă, Ioan Bogdan; Domocoș, Daniela; Voiţă-Mekereş, Florica (Frontiers in Public Health, 2023)
(1) Background: Scars are a natural consequence of the healing process, but with an impact on the psychological and social level of the individual, which can even lead to withdrawal and social stigmatization. We aimed to analyze the psychosocial impact determined by post-traumatic scars, using psychometric scales, to assess the effectiveness of the Mekereș' Psychosocial Internalization Scale (MPIS), and to identify relevant predictors of traumatic and surgical scar internalization. (2) Methods: our cohort included 293 participants, 149 women, and 144 men, aged 18 to 64 years of whom 153 had posttraumatic scars and 140 had surgical scars. Participants were screened for scar characteristics and completed a set of psychological scales. (3) Results: Relevant predictors for posttraumatic scar internalization (R2=0.721) are adaptation time, age of occurrence, and subjective appraisal, while for depression, and hopelessness relevant predictors are the subjective appraisal of the scars and the posttraumatic quality of life. (4) Conclusions: the psychological and social reporting of the aftermath of trauma, which has been followed by scarring, is an indicator of how a person will react and could indicate susceptibility to psychopathology.